2021
DOI: 10.3389/fncel.2021.696889
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and Its Role in Epilepsy

Abstract: Epilepsy is one of the most common symptoms of many neurological disorders. The typical excessive, synchronous and aberrant firing of neurons originating from different cerebral areas cause spontaneous recurrent epileptic seizures. Prolonged epilepsy can lead to neuronal damage and cell death. The mechanisms underlying epileptic pathogenesis and neuronal death remain unclear. Ferroptosis is a newly defined form of regulated cell death that is characterized by the overload of intracellular iron ions, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 94 publications
0
29
0
1
Order By: Relevance
“…Because of the lack of effective treatment, sequelae caused by neurological disorders have brought an enormous burden on society. Ferroptosis has been proved to be closely related to the occurrence and development of various neurological disorders [40][41][42][43]. Therefore, figuring out the role of ferroptosis in neurological disorders will provide an important basis for the treatment of diseases (Figure 1, Table 1).…”
Section: Ferroptosis In Neurological Disordersmentioning
confidence: 99%
“…Because of the lack of effective treatment, sequelae caused by neurological disorders have brought an enormous burden on society. Ferroptosis has been proved to be closely related to the occurrence and development of various neurological disorders [40][41][42][43]. Therefore, figuring out the role of ferroptosis in neurological disorders will provide an important basis for the treatment of diseases (Figure 1, Table 1).…”
Section: Ferroptosis In Neurological Disordersmentioning
confidence: 99%
“…Recent studies showed that the ferroptosis was not only related to chronic central nervous system diseases such as Alzheimer's disease, stroke, Parkinson's disease and Huntington's disease, but also palied a crucial role in epilepsy [20] . Recent study showed that inhibition of ferroptosis could alleviate the symptoms and improve the prognosis of epileptic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…As GSH acts as a major antioxidant in the brain, this impaired GSH redox status can lead to further oxidative damage and redox dysregulation, which is associated with cognitive deficits, neuronal death, and mortality in animal epilepsy models. Indeed, loss of glutathione peroxidase 4, a oxidation-resistant selenoprotein that utilizes GSH, leads to lipid peroxidation and subsequent ferroptosis, which is also found in epilepsy models ( Ingold et al, 2018 ; Cai and Yang, 2021 ).…”
Section: Oxidative Stress In Epilepsymentioning
confidence: 99%
“…In the reduced state, HMGB1 acts as a chemoattractant. In the oxidized state with two nearby cysteines forming a disulfide bond and the third cysteine unmodified, HMGB1 acts as a proinflammatory cytokine (Yang et al, 2021) which can interact with TLR4 (Balosso et al, 2014). Overoxidation inhibits all HMGB1 functions.…”
Section: Oxidative Stress and Redox Regulation Of Neuroinflammationmentioning
confidence: 99%